Optimalisasi Bandwidht dengan Metode Simple Queue pada Mikrotik (Studi Kasus : Heteroku Computer Bali) - I Wayan Darma Yasa, Darma; I Kadek Noppi Adi Jaya; Kadek Oky Sanjaya (RESI : Jurnal Riset Sistem Informasi, 2025)
This study discusses the optimization of bandwidth usage in the computer network of Heteroku Computer Bali by implementing the Simple Queue method on a Mikrotik Routerboard device. The main issue identified was the unequal distribution of bandwidth, which resulted in decreased network connection quality. The purpose of this study was to implement the Simple Queue method to optimize bandwidth usage and to analyze its impact on network stability. The research followed the stages of the Network Development Life Cycle, including analysis, design, simulation, implementation, and monitoring. Configuration was carried out by limiting Ether1 to Ether5 to 100 Mbps each. The test results showed an improvement in fair bandwidth distribution and more stable network connectivity. Thus, the implementation of the Simple Queue method successfully addressed the issue of bandwidth distribution and improved the overall network performance in the study environment.